Menu Rahmah - a preliminary review / Khairul Hidayat Rezo ... [et al.] - Rezo, Khairul Hidayat; Razali, Mohamad Azli; Zainol, Nooliza; Johari, Noorsa Riza (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
Ever since Menu Rahmah was introduced at the end of January 2023, it has received an overwhelming response from over 15,000 traders and food enthusiasts across Malaysia. Offering affordably priced meals at RM 5.00 or less, it provides balanced food options for breakfast, lunch, and dinner. Not limited to just rice-based dishes, the menu can also be diversified with items like noodles, pasta, and more. The program falls under the Ministry of Domestic Trade and Consumer Affairs (KPDNHEP) as a short-term initiative under the Rahmah umbrella to assist and address issues faced by the less privileged. The brainchild of the 10th Prime Minister, YAB Datuk Seri Anwar Ibrahim, it aims to tackle the rising cost of living and the economic crisis experienced by Malaysia, which consequently resulted in higher prices of goods and declining purchasing power.